Comparative study of Antihyperglycemic activity of aqueous extracts from the leaves of Bridelia ferruginea, Lophira lanceolata and Oxytenanthera abyssinica, with their mixture. - HOUNDJO, Camille F.; Agbodjogbe, Wilfrid; ASSOGBA, Fidèle M .; Kohoude, Midéko Justin; Ayedoun, Marc-Abel; Pierre H. Dansou, Pierre H. (My University, 2017)
Bridelia ferruginea, Lophira lanceolata and Oxytenanthera abyssinica are medicinal plants whose mixture is used for the treatment of diabetes by traditional medicine in Benin. The aim of this work is to evaluate the anti-hyperglycemic activity of each of these plants to their synergy of mixture extract on type 2 diabetes. The experiments performed in rabbits by oral glucose overload are showed that aqueous extracts of Bridelia ferruginea 500 mg / kg, Oxytenanthera abyssinica 1500 mg / kg and Lophira lanceolata 500 mg / kg are the most active. Of these extracts, Bridelia ferruginea (500 mg / kg, per os) significantly prevented oral glucose tolerance test (OGTT) as the glibenclamide reference product at 10 mg / kg. Decoctions of leaves of Bridelia ferruginea , Lophira lanceolata and Oxytenanthera abyssinica due to their antihyperglycemic effects, could therefore be used only in the traditional treatment of diabetes mellitus in Benin.
Keywords: Diabetes; phytochemistry; Bridelia ferruginea; Lophira lanceolata; Oxytenanthera abyssinica; antihyperglycemia.